The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsphotonics.1c01622
|View full text |Cite
|
Sign up to set email alerts
|

Telecom-Band Waveguide-Integrated MoS2 Photodetector Assisted by Hot Electrons

Abstract: We report a waveguide-integrated MoS2 photodetector operating at the telecom band, which is enabled by hot-electron-assisted photodetection. By integrating few-layer MoS2 on a silicon nitride waveguide and aligning one of the two Au electrodes on top of the waveguide, the evanescent field of the waveguide mode couples with the Au–MoS2 junction. Though MoS2 cannot absorb the telecom-band waveguide mode, the Au electrode could absorb it and generate hot electrons, which transfer to the beneath MoS2 channel due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 54 publications
0
29
2
Order By: Relevance
“…15 These handicaps conjointly lead to insufficient light absorption of 2DLM optoelectronic devices. To date, scientists and engineers have explored a variety of optical nano/micro-structures to ameliorate the photosensitivity of 2DLMs, including plasmonic optical antennas, 16 optical waveguides, 17 optical resonant cavities, 18 etc. However, these technologies suffer from their own shortcomings, such as exorbitant material cost, complicated manufacturing, limited enhancement factors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…15 These handicaps conjointly lead to insufficient light absorption of 2DLM optoelectronic devices. To date, scientists and engineers have explored a variety of optical nano/micro-structures to ameliorate the photosensitivity of 2DLMs, including plasmonic optical antennas, 16 optical waveguides, 17 optical resonant cavities, 18 etc. However, these technologies suffer from their own shortcomings, such as exorbitant material cost, complicated manufacturing, limited enhancement factors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…2(f). 15,16,18,[34][35][36][37][38][39] These comparisons have proven that the MoS2-based hot-electron photodetector constructed on the MRR possesses excellent electrical and optoelectronic properties.…”
mentioning
confidence: 90%
“…15 Recently, our group demonstrated a MoS2-based hot-electron photodetector integrated with an optical waveguide showing 15.7 mA W -1 at a wavelength of 1550 nm. 16 However, their performance could be further improved by utilizing novel device structure/design that enhance the responsivity through increasing light absorption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[36] In recent years, hot carrier injection mechanism have also been implemented in 2D material based PDs in order to achieve broadband photoresponses. [38][39][40] For example, Zhang et al reported a hot-electron photodetector based on an Au/MoS 2 hybrid structure integrated with a dielectric microring resonator, which exhibited a high responsivity of 154.6 mA W −1 at the NIR wavelength of 1516 nm. [38] These works provide insights that plasmonic resonance may also functionalize as a promising strategy to extend the response spectrum of 2D perovskite PDs via the generation of hot carriers.…”
mentioning
confidence: 99%